All systems go again - Pederick, Ben; Garner, Simon; Boland, Michael; ideo Education Australasia (Australia : Video Education Australasia, 2006)
Is a fast-moving and lively exploration of the three human energy systems, ATP-PC, Lactic and Aerobic. Providing an insight into how the body uses energy as quickly and as efficiently as possible to produce a variety of complex movements
Title from title screen
Executive producer : Mark McAuliffe ; senior producer : Richard Leigh ; graphics : Jeremy Lines, Reece Sanders ; sound : Wayne Martin, Alexy Gudimenko ; camera : Ben Pederick, Zane Loritt
Voice over : Mark Collard
Keywords: Muscles; Human biology; Human body parts and systems